Impact of Tool Geometry and Tool Feed on Machining Stability - Dassanayake, Achala V.; Suh, C. Steve (Journal of Vibration Testing and System Dynamics, 2026)
Tool-workpiece dynamics is characterized by aperiodic responses in- cluding period-doubling bifurcation and chaos. As a state signifying the extent of machining instability, tool chatter in longitudinal turn- ing operation is a function of nonlinear regenerative cutting force, instantaneous depth-of-cut (DOC), and workpiece whirling. The ef- fects of tool geometry and feed rate per revolution on cutting stability are investigated using a comprehensive model previously reported in References [1–3]. The model configuration allows the coupled tool- workpiece motion relative to the machining surface to be studied in the Cartesian space as a function of spindle speed, instantaneous DOC, rate of material removal, tool geometry, and material imbal- ance induced whirling. It is found that chatter can be eminent using one set of tool geometry while, at the same DOC, be sufficiently sup- pressed by employing tool inserts of different geometric parameters. Nonlinearity of tool structure is shown to have a dominant effect on tool vibration amplitude. High feed rate contributes to stability at high DOCs, thus indicating that feed rate is among the parameters that impact cutting stability.